Problematika Pembelajaran Bahwa Arab Pada Tingkat Sekolah Dasar - Silvia Nur Aulia, Elsa (2014)
This thesis discusses the problem of Arabic learning in the fourth grade of Al-Irsyad Satya Elementary School Kota Baru Parahyangan. The researcher focuses on the curriculum the methodology, and the evaluation technique of Arabic learning in Al-Irsyad Satya Elementary School Kota Baru Parahyangan.The purpose of this research is to find the matter of Arabic learning observed by its curriculum and study capability of students, its methodology which is observed by students progress and the subject's matter aspect, and also to find the evaluation of learning which observed by Arabic learning purpose aspect. This research was conducted by using a qualitative approach through analysis descriptive qualitative method. The research uses some accumulative data techniques, which are: (a) observation (b) direct interview of teachers, and the students of fourth grade in Al-Irsyad Satya, and (c) documentation study. The research analysis reduces data, displays data, and also conclusion drawing/verification.The conclusions of this research are : (a) the curriculum of Al-Irsyad Satya Elementary School hasn't been completed yet and there's no implementation of learning concept for each lesson, while the subject's matter of Arabic learning has suitable with capability of students, (b) the learning method used by the teachers is suitable for students's progress and subject's matter of Arabic learning, and (c) the learning evaluation is also suitable with the learning purpose. The recommendation for Al-Irsyad Satya Elementary School is to make a good Arabic learning curriculum in accordance with curriculum arrangement standard, increase the duration of Arabic learning, and also improve the media of Arabic learning. Permasalahan dalam penelitian ini adalah problematika pembelajaran bahasa Arab pada kelas IV di sekolah dasar Al-Irsyad Satya Kota Baru Parahyangan. Peneliti memfokuskan penelitian ini kepada kurikulum pembelajaran bahasa Arab, metodologi pembelajaran bahasa Arab, serta teknik evaluasi pembelajaran bahasa Arab di sekolah dasar Al-Irsyad Satya Kota Baru Parahyangan. Adapun tujuan dari penelitian ini adalah untuk mengetahui materi pembelajaran bahasa Arab ditinjau dari kurikulum dan segi kemampuan siswa, untuk mengetahui metodologi pembelajaran bahasa Arab ditinjau dari segi perkembangan siswa dan materi ajar, serta untuk mengetahui evaluasi pembelajaran ditinjau dari segi tujuan pembelajaran bahasa Arab.Dalam penelitian ini peneliti menggunakan pendekatan kualitatif dengan menggunakan metode penelitian analisis dekriptif kualitatif. Adapun teknik pengumpulan data yang dilakukan oleh peneliti yakni, (a) observasi (b) wawancara kepada bidang kurikulum, guru, murid dan kelas IV sekolah dasar Al-Irsyad Satya, (c) studi dokumentasi. Peneliti menganalisis data dengan cara mereduksi data, display data, dan conclusion drawing/ verification. Adapun dari hasil penelitian dan pembahasan maka dapat diambil kesimpulan bahwasanya (a) kurikulum di sekolah dasar Al-Irsyad Satya belum lengkap serta belum ada rencana pelaksanaan pembelajaran untuk setiap pembelajarannya, sedangkan materi pembelajaran bahasa Arab sudah sesuai dengan kemampuan siswa, (b) metode pembelajaran yang digunakan oleh guru sesuai dengan perkembangan siswa dan materi pembelajaran bahasa Arab, (c) evaluasi pembelajaran sudah sesuai dengan tujuan pembelajaran bahasa Arab. Rekomendasi peneliti adalah agar sekolah dasar Al-Irsyad Satya membuat kurikulum untuk pembelajaran bahasa Arab yang baik dan benar sesuai denan standar penyusunan kurikum serta menambah durasi pembelajaran bahasa Arab, serta mengembangkan media pembelajaran bahasa Arab.